Multinationals And The Bargaining Dynamic Among Least Developed Countries - Fernandez, Mauricio Lascurain; Valdés, Luiz Fernando Villafuerte (Faculdade de Filosofia e Ciências, 2018)
Most of the twentieth century, relations among multinational companies and the governments of the Least Developed Countries (LDCs) were seen as conflictive, mainly in the extractive sector, as the former were considered as highly exploitative. However, this vision has evolved by two essential factors: a) the acceleration of the process of economic globalization in the last 30 years and b) certain advantages LCDs have promoted to foster economic growth at the moment Multinationals Companies (MNCs) are installed in their territories. The major concern of national governments in the LDCs is that some MNCs have greater influence and negotiation power than governments themselves because of the infrastructure deficiencies and competitive advantages, placing them in an unfavorable position at the time to negotiate with MNCs. This paper tries to identify the bargaining dynamic among multinationals and LDC governments, and the effects on the latter ones. Key words: Foreign Direct Investment, Bargaining strategies, Economic globalization, least development countries, Theoretical approaches. Number of classification: JEL: F23, F51, F02, O10, B49     Recebido em: abril/2017. Aprobado em: maio/2017.